2023
DOI: 10.3389/frph.2023.1151179
|View full text |Cite
|
Sign up to set email alerts
|

The impact of health education interventions on HPV vaccination uptake, awareness, and acceptance among people under 30 years old in India: a literature review with systematic search

Abstract: BackgroundThe HPV vaccine is used as one of the main prevention tools for HPV-related cancers globally, yet it is not part of the Indian National Immunization program. In light of the introduction of the indigenous vaccine, we examine the effectiveness of health education about uptake, acceptance, and awareness.MethodsResearch was performed in the following databases: PubMed, CINAHL, Scopus, and Embase to identify studies between 2008 and 2022. Studies were included if: they were conducted in India including p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
2
0
1
Order By: Relevance
“…Participants expressed a strong belief (82.8%) in the need for educational sessions to increase awareness about the HPV vaccine in their community. This finding highlights the perceived value of community-based educational initiatives, which have been shown to improve knowledge and vaccine acceptance [ 25 , 26 ]. It underscores the importance of implementing educational programs to bridge the knowledge gap and enhance community acceptance of HPV vaccination.…”
Section: Discussionmentioning
confidence: 87%
“…Participants expressed a strong belief (82.8%) in the need for educational sessions to increase awareness about the HPV vaccine in their community. This finding highlights the perceived value of community-based educational initiatives, which have been shown to improve knowledge and vaccine acceptance [ 25 , 26 ]. It underscores the importance of implementing educational programs to bridge the knowledge gap and enhance community acceptance of HPV vaccination.…”
Section: Discussionmentioning
confidence: 87%
“…However, there is mixed evidence on the value of education strategies to increase the uptake of interventions generally and for HPV vaccination [ 71 ]. A recent systematic review carried out in India to measure the impact of educational interventions identified three studies focusing on educational interventions, and only one of these showed an increase in HPV vaccine uptake [ 72 ]. Contrary to this, a systematic review conducted in the USA reported that education by authoritative sources to parents increased HPV vaccine uptake by youths [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dengan demikian, kegiatan edukasi kesehatan terbukti dapat meningkatkan pengetahuan peserta edukasi terkait vaksinasi HPV untuk mencegah kanker serviks. Literatur sebelumnya juga menjelaskan bahwa kegiatan intervensi berupa edukasi kesehatan, dapat meningkatkan pengetahuan peserta sesuai dengan topik yang disampaikan (Krokidi et al, 2023;Samaria, 2022;Samaria, Alita, et al, 2020;Samaria et al, 2019;Thanasas et al, 2022). Oleh karena itu, tim pengabdian masyarakat memberikan rekomendasi kepada pihak sekolah untuk dapat memberikan program intervensi edukasi serupa bagi para siswi agar pengetahuan mereka tentang kesehatan reproduksi semakin meningkat.…”
Section: B Pembahasanunclassified